Prevalence of Eimeria Spp. Among Goats in China: A Systematic Review and Meta-Analysis - Diao, Nai-Chao; Zhao, Bo; Chen, Yu; Wang, Qi; Chen, Zi-Yang; Yang, Yang; Sun, Yu-Han; Shi, Jun-Feng; Li, Jian-Ming; Shi, Kun; Gong, Qing-Long; Du, Rui (Frontiers in Cellular and Infection Microbiology, 2022)
Eimeria spp. infection can cause weight loss in goats, and severe cases can lead to the death of lambs, resulting in economic losses to the goat industry. To explore the pooled prevalence of Eimeria spp. in goats in China, we obtained 70 related publications from five databases and conducted a meta-analysis. In China, the combined prevalence of Eimeria spp. in goats was 78.7% (95% confidence interval (CI): 68.15–87.67). Among them, the most serious infections occurred in Northeast China (88.0%, 95% CI: 83.54–91.86). The main Eimeria species were E. alijevi (43.7%, 95% CI: 29.53–58.45), E. arloingi (49.7%, 95% CI: 34.83–64.49), E. christenseni (41.2%, 95% CI: 27.07–56.16), and E. ninakohlyakimovae (35.9%, 95% CI: 21.02–52.31). In the sampling year subgroup, 2006 or later presented a lower prevalence (75.3%, 95%CI: 58.72–88.72). In terms of age, the point estimate for young goats (≤ 1 year) was higher (89.9%, 95% CI: 80.82–96.48). The Float (NaCl) method showed the lowest prevalence of Eimeria spp. in goats (75.9%, 95%CI: 62.00–87.46). In the season subgroup, the highest prevalence was in summer (81.5%, 95%CI: 49.62–99.18). Female goats presented a higher prevalence of Eimeria spp. infection than male goats (70.7%, 95%CI: 27.90–98.96). The prevalence was lower in the intensive feeding model (77.4%, 95%CI: 66.56–86.67) and higher in free feeding goats (79.4%, 95%CI: 66.46–89.92). In addition, we also analyzed the potential relationship between geographical factors and the prevalence of Eimeria spp. infection in goats in China. Our findings suggested that Eimeria spp. infection in goats is widespread in China. Despite the overall downward trend, this infection cannot be ignored. We recommend that breeders use anticoccidial drugs to prevent and treat this disease, while improving the feeding conditions and managemental practices to reduce the economic losses caused by Eimeria infection to the goat industry.